A system that reconstructs a 3D trajectory of a table tennis ball for performance analysis in table tennis - Tamaki, S. (Journal of the Japan Society for Precision Engineering, 2013)
In this paper, a method to reconstruct 3D trajectory of a table tennis ball and two systems that obtain shot information for table tennis performance analysis are proposed. The method and the systems are developed to solve the problem of conventional performance analysis in table tennis. There are several methods to reconstruct 2D ball trajectory or 3D trajectory of the heavy ball compares to a table tennis ball. However, the methods cannot be adopted for 3D trajectory reconstruction of a table tennis ball, because there are problems attribute to the dimension of a trajectory and the weight of a ball. The proposed method in this paper can reconstruct 3D trajectory of a table tennis ball. The key feature of the method is to approximate that a ball travels on tilted planes. The approximation makes the reconstruction robust against failure to measure 3D ball positions in some frames. Based on the proposed method, a system using two RGB cameras is developed. The system is experimentally verified that it can provide accurate information for match analysis. Next, a system using an RGB-D camera is developed to optimize usability for practitioners. The system is experimentally verified that it can provide accurate information for service analysis.